The dawn of world redemption a survey of historical revelation in the Old Testament - Sauer, Erich, 1898-1959; Lang, George Henry 1874-1958 (Exeter, UK Paternoster, 1956)
Includes bibliographical references and index.
Brethren writer. Originally published 1951
Keywords: Bible. O.T. -- historical revelation